Adaptation of Mycobacterium smegmatis to an industrial scale medium and isolation of the mycobacterial porinMspA - Wendel, Sebastian O.; Perera, Ayomi S.; Pfromm, Peter H.; Czermak, Peter; Bossmann, Stefan H. (My University, 2013)
The adaptation of the organism to a simple and cost-effective growth medium is mandatory in developing a process for large scale production of the octamericporinMspA, which is isolated from Mycobacterium smegmatis. A fermentation optimization with the minimal nutrients required for growth has been performed. During the fermentation, the iron- and ammonium chloride concentrations in the medium were varied to determine their impact on the observed growth rates and cell mass yields. Common antibiotics to control contamination were eliminated in favor of copper sulfate to reduce costs. MspA has been successfully isolated from the harvested M. smegmatisusing aqueous nOPOE (noctyloligooxyethylene) at 65°C. Because of the extraordinary stability of MspA, it is possible to denature and precipitate virtually all other proteins and contaminants by following this approach. To further purify the product, acetone is used for precipitation. Gel electrophoresis confirmed the presence and purity of MspA. A maximum of 840µg (via Bradford assay) of pure MspA per liter of the optimized simple growth medium has been obtained. This is a 40% increase with respect to the previously reported culture medium for MspA.
Keywords: Medium; Optimization; Mycobacterium; Smegmatis; MspA; Protein extraction